Development of quality measures to assess tooth decay outcomes from electronic health record data. (12th October 2022) - Brandon, Ryan G.; Bangar, Suhasini; Yansane, Alfa; Neumann, Ana; Mullins, Joanna M.; Kalenderian, Elsbeth; Walji, Muhammad F.; White, Joel M.
Abstract: Objectives: To develop outcomes of care quality measures derived from the dental electronic health record (EHR) to assess the occurrence and timely treatment of tooth decay. Methods: Quality measures were developed to assess whether decay was treated within 6 months and if new decay occurred in patients seen. Using EHR‐derived data of the state of each tooth surface, algorithms compared the patient's teeth at different dates to determine if decay was treated or new decay had occurred. Manual chart reviews were conducted at three sites to validate the measures. The measures were implemented and scores were calculated for three sites over four calendar years, 2016 through 2019. Results: About 954 charts were manually reviewed for the timely treatment of tooth decay measure, with measure performance of sensitivity 97%, specificity 85%, positive predictive value (PPV) 91%, negative predictive value (NPV) 95%. About 739 charts were reviewed for new decay measure, with sensitivity 94%, specificity 99%, PPV 99%, and NPV 94%. Across all sites and years, 52.8% of patients with decay were fully treated within 6 months of diagnosis ( n = 247, 959). A total of 23.8% of patients experienced new decay, measured at an annual exam ( n = 640, 004). Conclusion: Methods were developed and validated for assessing timely treatment of decay and occurrence of new decay derived from EHR data, creating effective outcome measures. These EHR‐based quality measures produce accurate and reliable results that support efforts and advancement in quality assessment, quality improvement, patient care and research.